Wilga 2019 – Photonics Applications - Romaniuk, Ryszard S. (Photonics Letters of Poland, 2019)
Wilga Symposium on Photonics Applications [1] has been serving the national and international communities of young researchers since nearly a quarter of the century. Ph.D. students, active in photonics research and technology, optoelectronics, optical engineering, and associated fields like electronics, materials engineering, mechatronics, and ITC present successive developments of their work. The subjects embrace optical fiber technology, optical communications, sensors, light sources and lighting, research and industrial applications. Since its beginning Wilga has gathered more than 5000 presentations by Ph.D. students, out of which around 3000 were published internationally in the Proceedings of SPIE [2-5]. The paper digests concisely some of the achievements of Wilga2019 [6] on occasion of the 10th Anniversary of the Photonics Letters of Poland. Wilga Symposium on Photonics Applications is a very important pillar of the PSP Society focusing strongly its interest on young photonics researchers. Full Text: PDF References WILGA Symposium on Photonics Applications web page: [wilga.ise.pw.edu.pl] DirectLink R.S. Romaniuk, K.T. Pozniak, "HOST: hybrid optoelectronic versatile telemetric system for local community", Proc. SPIE 5125 (2002). CrossRef R.S. Romaniuk, "Optical fibers and photonics applications: topical tracks at Wilga conferences", Proc. SPIE 8698, 86980S (2012). CrossRef R.S. Romaniuk, "Photonics Applications and Web Engineering: WILGA 2018", Proc. SPIE 10808, 1080802 (2018). CrossRef R.S. Romaniuk, "Advanced Photonic and Electronic Systems WILGA 2018", Int. Journ. on Electronics and Telecommunications, IJET 64, 3 (2018). CrossRef R.S. Romaniuk, M. Linczuk, "Offsetting, relations, and blending with perturbation functions", Photonics applications in astronomy, communications, industry and high energy physics experiments, Proc. SPIE 11176 (2019). CrossRef